Penggerombolan provinsi di Indonesia berdasarkan instrumen akreditasi satuan pendidikan jenjang SMK menggunakan K-means dan average linkage - Fahriya, Andina; Sembiring, Febryna; Susetyo, Budi (Majalah Ilmiah Matematika dan Statistika, 2024)
Improvement and updates need to be done in order to maintain the existence of a school. Accreditation is one of the references to assess the excellence of a school. There are several components used in the accreditation assessment included in the IASP, namely Graduate Quality, Learning Process, Teacher Quality, and School Management. Additionally, to determine which provinces have low, medium, or high IASP scores, clustering is performed on the IASP scores of those provinces. Cluster analysis is a method used to group research objects based on similarities in their characteristics. In this study, clustering was performed using the K-means and average linkage methods on the average IASP scores of vocational high schools (SMK) in 34 provinces in Indonesia. With the Elbow Criterion approach, four clusters were formed for each method. The results of Dunn Index showed that the average linkage method performed better in clustering compared to the K-Means method. Keywords: IASP, Cluster Analysis, K-Means, Average LinkageMSC2020: 62H30